Transient Activation of Hematopoietic Stem and Progenitor Cells by IFNγ during Acute Bacterial Infection - MacNamara, Katherine C. (Public Library of Science, 2011)
How hematopoietic stem cells (HSCs) respond to inflammatory signals during infections is not well understood. Our studies have used a murine model of ehrlichiosis, an emerging tick-born disease, to address how infection impacts hematopoietic function. Infection of C57BL/6 mice with the intracellular bacterium, Ehrlichia muris, results in anemia and thrombocytopenia, similar to what is observed in human ehrlichiosis patients. In the mouse, infection promotes myelopoiesis, a process that is critically dependent on interferon gamma (IFNγ) signaling. In the present study, we demonstrate that E. muris infection also drives the transient proliferation and expansion of bone marrow Lin-negative Sca-1(+) cKit(+) (LSK) cells, a population of progenitor cells that contains HSCs. Expansion of the LSK population in the bone marrow was associated with a loss of dormant, long-term repopulating HSCs, reduced engraftment, and a bias towards myeloid lineage differentiation within that population. The reduced engraftment and myeloid bias of the infection-induced LSK cells was transient, and was most pronounced on day 8 post-infection. The infection-induced changes were accompanied by an expansion of more differentiated multipotent progenitor cells, and required IFNγ signaling. Thus, in response to inflammatory signals elicited during acute infection, HSCs can undergo a rapid, IFNγ-dependent, transient shift from dormancy to activity, ostensibly, to provide the host with additional or better-armed innate cells for host defense. Similar changes in hematopoietic function likely underlie many different infections of public health importance.